A link between the newly described colistin resistance gene mcr-9 and clinical Enterobacteriaceae isolates carrying blaSHV-12 from horses in Sweden. (March 2020) - Börjesson, Stefan; Greko, Christina; Myrenås, Mattias; Landén, Annica; Nilsson, Oskar; Pedersen, Karl
Highlights: mcr-9 is common among clinical ESBL-producing Enterobacteriaceae isolates from horses in Sweden. mcr-9 appears linked to bla SHV-12 and plasmid replicon types IncHI2 and IncHI2A. The potential regulatory genes qseB - and qseC -like for mcr-9 were not detected. Spread of mcr-9 is mainly horizontal, but some clonal dissemination was observed. All mcr-9 -positive isolates carried resistance genes to all antibiotics authorised for treatment of horses in Sweden. Abstract: Objectives: The aim of this study was to investigate the occurrence of the newly described transferable colistin resistance gene mcr-9 in extended-spectrum β-lactamase (ESBL)-producing clinical Enterobacteriaceae isolates from horses in Sweden. Methods: A total of 56 whole-genome sequenced ESBL-producing Enterobacteriaceae isolates from horses were subjected to in silico detection of antimicrobial resistance genes and identification of plasmid replicons types. The colistin minimum inhibitory concentration (MIC) for mcr -positive isolates was determined by broth microdilution. Relatedness between Enterobacteriaceae carrying mcr genes was determined by multilocus sequence typing (MLST) and core genome MLST. Results: Thirty ESBL-producing Enterobacteriaceae isolates from horses were positive for the colistin resistance gene mcr-9 . These isolates included Enterobacter cloacae, Escherichia coli, Klebsiella oxytoca and Citrobacter freundii and belonged to diverse MLST sequence types within each species. Two of the mcr-9 -containing isolates originated from the same horse. All mcr-9 -positive isolates had colistin MICs below or equal to the EUCAST epidemiological cut-off value of 2 mg/L and were negative for the two potential regulatory genes qseB -like and qseC -like for mcr-9 . Except for one isolate carrying only bla TEM - 1B, all of the isolates carried bla SHV-12 and bla TEM-1B, and were all considered multidrug-resistant as they harboured genes encoding resistance to aminoglycosides, chloramphenicol, fosfomycin, macrolides, quinolones, sulfonamides, trimethoprim and tetracyclines. Plasmid replicon types IncHI2 and IncHI2A were detected in all mcr-9 -positive isolates. Conclusion: The occurrence of mcr-9 was common among clinical ESBL-producing Enterobacteriaceae isolates from horses in Sweden and was linked to the ESBL-encoding gene bla SHV-12 and plasmid replicon types IncHI2 and IncHI2A.